Green Digital Transformation Capability Dan Sustainable Organizational Performance Pada Perguruan Tinggi Di Kota Makassar: Peran Mediasi Green Digital Innovation Dan Moderasi Data-Driven Culture - Dhimas Tribuana; Andi Firdania; Muh. Rusli; Abu Said Uddin; Herlina Amin Noor; Natsir Thamrin (Plexi Digital Indonesia, 2026)
This study examines the effects of Green Digital Transformation Capability (GDTC) on Sustainable Organizational Performance (SOP) in higher education through Green Digital Innovation (GDI), while assessing Data-Driven Culture (DDC) as a moderating condition. A quantitative cross-sectional survey was conducted among 200 lecturers and educational staff at higher education institutions in Makassar City, Indonesia, from 1 to 14 April 2026. Data were analyzed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 4 and 5,000 bootstrap subsamples. The measurement model demonstrated satisfactory reliability and validity (outer loadings = 0.738-0.868; composite reliability = 0.923-0.938; AVE = 0.624-0.689; HTMT = 0.182-0.659). GDTC positively affected GDI (beta = 0.443; p < 0.001) and SOP (beta = 0.302; p < 0.001), while GDI positively affected SOP (beta = 0.372; p < 0.001). DDC positively affected GDI (beta = 0.234; p < 0.001) and SOP (beta = 0.274; p < 0.001). GDI partially mediated the GDTC-SOP relationship (beta = 0.165; p < 0.001), and DDC strengthened the GDTC-GDI relationship (beta = 0.388; p < 0.001). The model explained 42.7% of GDI and 50.4% of SOP variance. The findings extend digital sustainability research by demonstrating a capability-innovation-performance mechanism and identifying data-driven culture as a boundary condition in higher education.